2004
DOI: 10.1016/j.geoforum.2004.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Determining factors of the development of a national financial center: the case of China

Abstract: This study explores, theoretically and empirically, one of the important issues of the geography of finance: the location of high-level financial services. Specifically, we will try to explain why foreign financial services are spatially concentrated on a particular city to form a national financial center in China. By reviewing various forces behind the formation of a financial center, we argue that information problems have created the necessity of the geographic agglomeration of financial activities in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(52 citation statements)
references
References 10 publications
2
50
0
Order By: Relevance
“…Although all giant state-owned banks (e.g. Bank of China, China Construction Bank, and Industrial and Commercial Bank of China) are headquartered in Beijing, the bulk of the domestic and offshore financial activities are carried out in the triad of Hong Kong, Shanghai, and Shenzhen (Zhao, 2003;Zhao et al, 2004;KPMG, 2011;Lai, 2012). On the other hand, Beijing-based banks control large amount of assets: in 2015, the combined assets of nine of Beijing's major and regional banks ranked by Forbes exceeded $13,343 billion, more than that of any other financial centres in the world, even three times more than Japan's GDP (7).…”
Section: The Rise Of Beijing and The Sources Of Its Powermentioning
confidence: 99%
“…Although all giant state-owned banks (e.g. Bank of China, China Construction Bank, and Industrial and Commercial Bank of China) are headquartered in Beijing, the bulk of the domestic and offshore financial activities are carried out in the triad of Hong Kong, Shanghai, and Shenzhen (Zhao, 2003;Zhao et al, 2004;KPMG, 2011;Lai, 2012). On the other hand, Beijing-based banks control large amount of assets: in 2015, the combined assets of nine of Beijing's major and regional banks ranked by Forbes exceeded $13,343 billion, more than that of any other financial centres in the world, even three times more than Japan's GDP (7).…”
Section: The Rise Of Beijing and The Sources Of Its Powermentioning
confidence: 99%
“…Meanwhile, other Chinese cities equally fare well, with Hong Kong, Shanghai, Shenzhen, Guangzhou, Changsa and Foshan also featuring amongst the cities with the largest gains in CAC. However, although we are clearly witnessing a quasi-general rise of Chinese cities in their level of CAC, it is also clear that this growth is firmly focused on a limited set of cities, with especially Beijing, Shanghai, Hong Kong, Guangzhou and Shenzhen emerging as 'the big 5' (with particularly the first three cities dominating) (see also Zhao et al, 2004;Zhao et al, 2005).…”
Section: Command and Control Centres In The Asia-pacific Regionmentioning
confidence: 99%
“…Luintel et al (2008) found that financial structure and financial development significantly affect the output level of most countries. It is necessary to create a geography agglomeration of financial activities due to information problems, and a financial center could be its platform (Zhao et al 2004). Cobb (1998) provided evidence that the global major financial centers, such as New York, London, and Tokyo, have good financial services.…”
Section: Introductionmentioning
confidence: 99%